Pelatihan Pembuatan Pupuk Bokhasi pada Kelompok Tani Ternak di Desa Wuasa Kecamatan Lore Utara Kabupaten Poso - Fabian Amir Djafar; Uti Nopriani; Marten Pangli; Suwardhi Pantih; Erwin Taroreh (Batara Wisnu : Indonesian Journal of Community Services, 2021)
This community service project aims to improve farmer groups bokashi fertilizer-making skills and professionalism. This community service activity is the method used in the approach and assistance by survey, lecture, discussion, question and answer, and training. This service activity aims to train farmer groups to produce bokashi fertilizer. The results of this activity showed that farmers group in Wuasa Village have new knowledge and skills in making bokashi fertilizer